Analisis kelayakan media pembelajaran buku cerita digital berbasis audio-visual pada pembelajaran ilmu pengetahuan sosial - Mahdiyah, Rohadatul Aisy (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the feasibility of audio-visual-based digital storybook learning media in social studies learning on the material of socio-cultural diversity of society. The research method used is a mix method with quantitative and qualitative data analysis techniques. Quantitative data is based on the results of expert validator media assessments, while qualitative data is based on comments and suggestions. The results of the media expert assessment were 94.3%, material experts 77.3% and practitioner experts 88.6%, resulting in an overall average presentation of 86.73% which indicates that the audio-visual-based digital storybook learning media is very valid for testing. In addition, there are several inputs provided by the validators, such as layout improvements, the addition of cultural elements, readjustment of regional accents, and the addition of student practice activities. Thus, audio-visual-based digital storybook learning media is considered effective in learning as an interactive, interesting, and contextual learning medium.